2001
DOI: 10.1083/jcb.200105081
|View full text |Cite
|
Sign up to set email alerts
|

α-Toxin is a mediator of Staphylococcus aureus–induced cell death and activates caspases via the intrinsic death pathway independently of death receptor signaling

Abstract: Infections with Staphylococcus aureus, a common inducer of septic and toxic shock, often result in tissue damage and death of various cell types. Although S. aureus was suggested to induce apoptosis, the underlying signal transduction pathways remained elusive. We show that caspase activation and DNA fragmentation were induced not only when Jurkat T cells were infected with intact bacteria, but also after treatment with supernatants of various S. aureus strains. We also demonstrate that S. aureus–induced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
179
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 58 publications
(68 reference statements)
17
179
2
Order By: Relevance
“…To investigate this hypothesis in more detail, we first analyzed hypodiploid nuclei formation induced by either a-toxin or by a supernatant of the cytotoxic S. aureus strain Wood 46 in the absence or presence of the broad spectrum caspase inhibitor zVAD-fmk. Similar to the results obtained with Jurkat Bcl-2 cells, 32 32 ), zVAD-fmk reduced hypodiploid nuclei formation by only 22 and 40%, respectively. In contrast, CD95-induced DNA fragmentation in Jurkat cells was almost completely blocked in the presence of zVAD-fmk ( Figure 1a).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…To investigate this hypothesis in more detail, we first analyzed hypodiploid nuclei formation induced by either a-toxin or by a supernatant of the cytotoxic S. aureus strain Wood 46 in the absence or presence of the broad spectrum caspase inhibitor zVAD-fmk. Similar to the results obtained with Jurkat Bcl-2 cells, 32 32 ), zVAD-fmk reduced hypodiploid nuclei formation by only 22 and 40%, respectively. In contrast, CD95-induced DNA fragmentation in Jurkat cells was almost completely blocked in the presence of zVAD-fmk ( Figure 1a).…”
Section: Resultssupporting
confidence: 85%
“…32 During this work, however, we also noticed that although S. aureusinduced caspase activation was almost completely blocked in Bcl-2-overexpressing Jurkat cells, the formation of hypodiploid nuclei as measured by FACS analysis could only be partially prevented in these cells. These results indicated that caspases might not be required for S. aureus-induced DNA fragmentation and cell death.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…18,21,41,[55][56][57][58][59][60][61][62][63][64] Viruses exploit apoptotic processes as well, especially reducing the death of virally infected cells to facilitate intracellular viral replication. The viral reprogramming of cell death, in contrast, reflects a distinct approach.…”
Section: Reprogrammed Cell Deathmentioning
confidence: 99%
“…The leukotoxin γ-hemolysin targets red blood cells and can cause massive hemolysis [50], while the monomeric α-toxin (or α-hemolysin) is highly cytotoxic and polymerizes to form a water channel in host cell membranes [51]. This leukotoxin leads to apoptosis through activation of a caspase cascade [52]. These leukotoxins extend bacterial infection by eliminating predatory immune cells and enhancing invasion of host tissue.…”
Section: As a Primarily Extracellular Pathogen The Microbial Surfacementioning
confidence: 99%